Akta 126:: Akta Cukai Spekulasi Tanah, 1974 & Land Speculation Tax Act, 1974 - Singh, Jaginder (Journal of Malaysian and Comparative Law, 2018)
Akta 126: Akta Cukai Spekulasi Tanah, 1974 & Land Speculation Tax Act, 1974